A Holistic Integral Safety Assurance Approach to Aircraft Digital System Development Process - Loris Dal Lago; Janet J. Liu (Engineering Proceedings, 2025)
The maturation of system engineering practices to support the regulatory landscape and handle novel application domains, such as hybrid-electric distribution systems, calls for new ways to support development assurance objectives and end-to-end safety. In this paper, we build on the concept of a knowledge base of safety assurance methods to guide users in framing the problem space and discover existing and novel digital solutions to tackle safety assurance challenges. The proposed approach offers users with different skills, roles, objectives and experience ways to identify relevant use case solutions for traditional and novel aerospace applications.